Clinical and etiological profile of thrombocytopenia in adults: A tertiary-care hospital-based cross-sectional study - Shruti K Bhalara; Smita Shah; Hansa Goswami; RN Gonsai (Universiti Kebangsaan Malaysia, 2015)
Background: The etiologies of thrombocytopenia are diverse. Various studies on thrombocytopenia are done in the past have related to specific etiologies. Objectives: This study attempts to determine the common etiologies of thrombocytopenia in adult patients admitted to Civil Hospital, Ahmedabad. Material and Methods: A cross-sectional study was carried out at Civil Hospital, Ahmedabad. Patients with thrombocytopenia more than 18 years of age at admission between 1 October and 31 October 2013 were followed up during their stay in hospital, diagnosis were made, and bleeding manifestations and requirement of platelet transfusion were recorded. Results: From the 412 patients studied, dengue was diagnosed in 28.6% of patients followed by malaria in 22.8%, chronic liver disease in 15.2%, hypersplenism in 12.3%, septicemia in 6.3%, gestational thrombocytopenia and disseminated intravascular coagulation in 5.5%, immune thrombocytopenic purpura (ITP) in 3.1%, megaloblastic anemia in 1.9%, human immunodeficiency virus in 1.4%, drug-induced thrombocytopenia in 1.2%, leukemia in 0.7%, and aplastic anemia in 0.48%. Bleeding secondary to thrombocytopenia was seen in 46 (11.2%) patients; of them, 28 were diagnosed with dengue fever, 4 with chronic liver disease, 3 with sepsis, 2 with hematological malignancies, and 9 with ITP. The common bleeding manifestations were gum bleed, purpura, petechial rash, and bruising. All the cases with platelet count o5,000/mL had bleeding manifestations secondary to thrombocytopenia. From the patients studied, 79.3% had fever associated with thrombocytopenia. Platelet transfusion was given to 87 patients: of these, 46 (52.8%) were transfused because of bleeding and 41 (47.1%) were given prophylactic transfusion. Conclusion: Dengue fever was the most common cause of thrombocytopenia and the most common etiology found in patients who had bleeding secondary to thrombocytopenia with gum bleed as a common manifestation. There was no definitive trigger value of platelet for platelet transfusion, and transfusion because of bleeding and prophylactic transfusion were given in almost similar proportions of patients.